PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS DAN DIVIDENDS PER SHARE TERHADAP RETURN SAHAM - Putria Ananda, Viska (JURNAL EKONOMI PERJUANGAN, 2025)
The objectives of this research was to know and analysize the firm size, profitability, dividend per share and stock returns in Manufacturing Companies Listed on the Indonesia Stock Exchange and the effect of firm size, profitability, and dividend per share on stock returns in Manufacturing Companies Listed on the Stock Exchange. Indonesia. The research method used in this research is descriptive analysis with a census approach. The data needed in this study is secondary documentary data containing the company's financial history published on the Indonesia Stock Exchange (IDX). The data and information obtained from the results of this study were analyzed using multiple regression analysis of panel data. Based on the results of the study, it was known that together firm size, profitability, and dividend per share have a positive effect on stock returns in Manufacturing Companies listed on the Indonesia Stock Exchange. Partially, firm size have a negative effect on stock returns, while profitability and and dividend per share has positive effect on stock returns. It was recommended for Manufacturing Companies to increase firm size, profitability and dividends per share so as to increase and increase stock returns.